EFEKTIVITAS BERBAGAI UMPAN PERANGKAP LALAT DI PASAR IKAN DAN PASAR TRADISIONAL - Hadi, Mochammad Choirul; Sujaya, I Nyoman; Habibah, Nur (JST (Jurnal Sains dan Teknologi), 2022)
The benefits of Methyl eugenol, a chemical used as an attractant, especially for fruit flies were interesting to develop. This study aimed was to compare flies that enter fly traps fed with Methyl eugenol, Methyl pyrazine, fish innards, and chicken innards. This research was a quasi-experimental type to examine the effectiveness of bait with four treatment groups. The bait was installed on fly traps made by the Research Team, which were placed at the Kedonganan Fish Market, Kuta, and the Phula Kerti Traditional Market, Denpasar. Each bait is placed in five different fly traps, or in a day 40 units are installed in both markets. The results show that there are different types of trapped flies. In the Fish Market, the most common types of flies are House flies (Musca domestica), while in the Traditional market there are many types of fruit flies (Bactrocera sp). The baits that flies prefer are also different, Musca domestica prefer chicken innards bait, while fruit flies prefer Methyl eugenol bait.